Você está na página 1de 67

 λ x 2 (a)α = a; (b)α = b/M

t

dy

dt

= 3y 2 + sen(t + y)

d 3 z

dt 3

= e z

+ t +

d 2 z

dt

2

y

1

y(t) = 2 sen(t) 3 cos(2t)

d 2 y

dt 2

+ y = cos(2t)

2

dt d 2 [2 sen(t) 3 cos(2t)] + [2 sen(t) 3 cos(2t)] = cos(2t)

1

1

dy

dt

= f(t, y)

y(t)

dy

dt

= h(t)

t

t

y =

h(t) dt + c

 dy 2t cos(y) + 3t 2 y dt = t 2 sen(y) − t 3 + y

dy

dt

+ a(t)y = b(t)

a(t) b(t) t

y

dy/dt = y 3 +sen(t) dy/dt = 3t+cos(y)

b(t) = 0

dy

dt

+ a(t)y = 0

b(t)

b(t) = 0

 dy dt = −a(t)y 1 y 1 dy y dt = a(t) d dt ln |y(t)| = −a(t)

t

ln |y(t)| =

a(t) dt + c 1

c 1

|y(t)| = e a(t) dt

+ c 1 = ce a(t) dt

=

y(t) = ce a(t) dt

c

 e −

dy

dt

+ y cos(t) = 0

a(t) = cos(t)

a(t) dt

= e cos(t) dt

= e sen(t) =

y(t) = ce sen(t)

y 0 t 0

dy

dt

+ a(t)y = 0

y(t 0 ) = y 0

t

t

0

ds ln |y(s)|ds =

t

0

d

t

a(s) ds

t

=ln |y(t)| − ln |y(t 0 )| =

t

0

a(s) ds

y(t)

y(t 0 )

= e

t

0

t

a(s) ds =

y(t 0 ) e

t

0

y(t)

t

a(s) ds

= 1

t = t 0

y(t 0 )

y(t 0 ) e

t 0

t 0

a(s) ds

= 1

t

y(t) = y(t 0 )e

t

0

a(s) ds

t

= y 0 e 0

t

a(s) ds

.

dy

dt

+ yt sen(t) = 0

y(0) = 2

t

a(t) = t sen(t) =

t

0

a(s) ds = t

0

s sen(s) ds .

t

0

s sen(s) ds = t cos(t) sen(t)

y(t) = 2e sen(t)t cos(t)

dy

dt

+ a(t)y = b(t)

b(t)

= 0

dt d ( ) = b(t)

t

µ(t)

µ(t) dy + µ(t)a(t)y = µ(t)b(t)

dt

d

dt µ(t)y

= µ(t) dy
dt

+

dt y.

µ(t) dy + µ(t)a(t)y = µ(t) dy

dt

dt

+

dt

y ⇐⇒ µ(t)a(t) =

dt

=

1

(t)

µ(t)

dt

= a(t) =

=µ(t) = e

a(t) dt .

µ(t)

dt d µ(t)y

= µ(t)b(t).

µ(t)y =

µ(t)b(t) dt + c =y(t) = e

(a(t)dt)

µ(t)b(t) dt + c.

y(t 0 ) = y 0

t

µ(t)y µ(t 0 )y 0 =

t

0

µ(s)b(s) ds =y(t) =

µ(t) µ(t 0 )y 0 +

1

t

t

0

µ(s)b(s) ds

µ(t)

dy

dt

+ t 2 y = t 2

t 3

a(t) = t 2 =µ(t) = e t 2 dt = e 3

d
3
t 3
3
)y = t 2 e
3
dt (e t

t 3

• 3 t 3

t

+ c =y(t) = 1 + ce

3

e 3 .y = e 3

dy

dt + y =

• 1 y(1) = 2

t 2 + 1

a(t) = 1 =µ(t) = e 1dt =µ(t) = e t =

dt d (e t y) =

e t

t 2 + 1

[1, t]

e t y(t) ey(1) = t

1

e s

s 2 ds =e t y 2e =

1

1 +

t

e

s

1 + s 2 ds

y(t) = e t 2e + t

1

e s

s 2 ds

1 +

N(t)

t

dN

dt

N

 dN dt = −λN

λ

λ

λ t 0 N(t 0 ) = N 0

 t N(t) = N(t 0 ).e −λ t 0 ds = N 0 .e −λ(t−t 0 ) N 0 = e −λ(t−t 0 ) =⇒ −λ(t − t 0 ) = ln N N 0 N N/N 0 = 1/2 (t − t 0 ) = ln(2)/λ = 0.6931/λ

ln(2)

λ

λ

(Pb 210 ) (Ra 226 )

Pb 210 Ra 226

Pb 210

y(t) Pb 210 t y 0

Pb 210 t 0 r(t)

Ra 226 t λ

 Po 210 Ra 226

Pb 210

dy

dt

= λy + r(t),

y(t 0 ) = y 0

300

1600 r(t) r

dt d e λt .y = re λt =e λt y(t) e λt 0 y 0 =

r

λ (e λt e λt 0 ) =

y(t) =

r

λ (1 e λ(tt 0 ) ) + y 0 e λ(tt 0 )

y(t) r y 0

t t 0

Pb 210 Ra 226

Pb 210 Ra 226

λy 0 t t 0 = 300

λy 0 = λy(t)e 300λ r(e 300λ 1)

λy 0 λy(t)

r e 300λ

(Po 210 ) Pb 210

e 300λ λ = ln(2)

22

e 300λ = e 300. ln(2)

150

22
= 2
11
λy 0 = (8.5)2 150
11
− 0.8(2 150
11
− 1) = 98050
λy 0 = (12.6)2 150
11
− 0.26(2 150
11
λy 0 = (10.3)2 150
11
− 0.3(2 150
11
λy 0 = (8.2)2 150
11
− 0.17(2 150
11
λy 0 = (1.5)2 150
11
− 1.4(2 150
11
− 1) = 1274.7
λy 0 = (5.2)2 150
11
− 6(2 150
11
− 1) = −10181

1) = 157134.1

1) = 127337.2

1) = 102251.7

λy 0

dy

dt

+ a(t)y = 0

y(t)

1

dy(t)

y(t)

dt

= a(t)

dt d ln |y(t)| = a(t),

y(t) = ce a(t) dt

dy

dt

=

g(t)

f(y)

f g

f(y) dy
dt

= g(t)

dt d F(y(t)) = g(t)

F f

F(y(t)) =

g(t) dt + c

c

y(t)

(1 + t 2 ) dy

dt

= 1 + y 2

 1 dy = 1 + y 2 dt

1

1 + t 2 =

d

dt arctg(y(t)) =

1

1 + t 2

y(t) = tg(arctg(t) + c) =y(t) =

tg(arctg(t)) + tg(c)

1 tg(arctg(t)) tg(c)

tg(c) = k

 y(t) = t + k 1 − tk e y dy dt − (t + t 3 ) = 0, e y dy dt = t + t 3 e y − e = t 2 2 + t 4 4 − 1 2 y(t) = ln e − 3 t 2 4 + 2

y(1) = 1

1

4

+

t 4

4

.

 dy at + by + m dt = ct + dy + n ,

a, b, c, d, m, n

• 0

at + by

ct + dy

=

t = T + h y = Y

+ k h k

 dy dY a(T + h) + b(Y + k) + m aT + bY + ah + bk + m dt = dt = c(T + h) + d(Y + k) + n = cT + dY + ch + dk + n

ah + bk + m = 0

ch + dk + n = 0

 ah + bk = −m (1) ch + dk = −n (2)

 cah + bck cah + adk = −mc (3) = −na (4) mc − na bn − md adk − bck = mc − na =⇒ k = h = ⇐⇒ ad − bc = 0 ad − bc ad − bc dy at + by = dt ct + dy ad − bc = 0

p(t) t

r(p, t)

dp

dt

rp(t)

r

dp(t)

dt

= ap(t),

a =

p 0 t 0

dp(t)

dt

= ap(t),

p(t 0 ) = p 0

p(t) = p 0 .e a(tt 0 )

p(t) = (3.34).10 9 e 0.02(t1965)

p(t) = (6.68)10 9

1

e 0.02(1965) 0

2 = e 0.02(t1965)

,

2 e 0.02t =t ln(2)

0.02

=t 34, 6 ,

 0 2 6 10

dp(t)

dt

= 0.4p,

p(0) = 2

p(t) = 2e 0.4t

bp 2 b

p 2

dp

dt

= ap bp 2

a b

a b

p

bp 2 ap p

bp 2

dp

dt

= ap bp 2 ,

p(t 0 ) = p 0

p

p

0

ar br 2 =

t

0

dr

t

ds

p

p

0

dr

=

ar br 2

p

a

1

p

0

1

a br dr

b

r

+

1
a ln p
p 0
a − bp 0
a − bp

= t t 0 =p(t) =

ap 0